Islam and Multiculturalism in The Charter of Medina (Socio-Historical Studies) - Durotun Nafisah; Khalid Mawardi; Nasrudin Nasrudin (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
Multiculturalism becomes an interesting study material when related to the issue of pluralism in the various social life of Muslims. This paper will examine the relationship between Islam and multiculturalism with the consideration that Islam as a doctrinal system derived from God's revelation, sometimes clashes with the development of the socio-cultural context of its adherents. The main problem of this study is how the multiculturalism of the Muslim community in the Prophet is reflected in the Medina Charter. This study aims to map the pattern of multiculturalism in communities in Yathrib city of Medina. The study was conducted with historical methods and socio-cultural approaches. This study found the following patterns of multiculturalism: First, the Muslim community in the period of the Prophet in Medina based on Arab culture, grew up with patterns that were accommodating to forms of racial, religious, and 'ashabiyyah qabailiyyah diversity. Second, the pattern of the Muslim community that developed during the Medina period encouraged the growth of Muslim acculturation of non-Muslim communities to strengthen the integrity and integrity of Madinah society. Third, the pattern of multiculturalism is more evident as the reality of pluralism in Muslim societies is shown by the role of interfaith and racial communities.